Increasing of Energy Quality of Waste Product with Trichoderma and Aspergillus - Suwandyastuti, SNO; Subarjo, B; Rimbawanto, EA; Prayitno, Prayitno; Irawan, I; Zubaidah, S (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 1999)
Biomasa of agricultural residues are potensial as ruminant feeds. However due it is low palatability, digestibility and nutritive value limited their use. In order to improve their use, treatment need to be applied. Biological treatment by using microba seems to be an alternative because of their capability with no pollution problems. The first experiment aims to select the microorganism which have a potensial to degrade the crude fiber, based the production of reduction sugar. The second experiment aims to improve the protein and amino acid on rice straw, cassava, waste, and rice husk, by inoculated the starter of Candida utilis and or Sacharomyces cerevise. The second experiment has been conducted on Animal Nutrition and Feed Laboratory, Faculty of Animal Husbandry UNSOED for eight month Fermentation trial has been done in semi solid media, by the method of Kjic (1964), in Batch System, Variables measure were: (1) reduction sugar, (2) cellulose, (3) protein, (4) amino acids, (5) cellulase activity, (6) essensial mineral and (7) energy. Based on the all variables measured that were conclused that the quality ofÂ rice straw can be improved by mixed culture ofÂ T, viride â S. cerevise, the rice husk by A. niger â C. utilis, T. viride â C. utilis and A. niger â S cerevise while for cassava waste byÂ A. niger â S. cerevise and A. niger â C. utilis Â (Animal Production 1(1) : 10-16 (1999).Â Key Words: Waste Product, Energy, Microorganism